2009
DOI: 10.1080/09583150802696517
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the biological control agentPhlebiopsis giganteaon its resident genetic structure in the Baltic Sea area

Abstract: The basidiomycete Phlebiopsis gigantea (Fr.) Jü lich has been used in Swedish forestry as a biocontrol agent against the root and butt-rot pathogen Heterobasidion annosum s.l. on freshly cut Picea abies stumps since the early 1990s. Until 2005, the commercial preparation of this biological stump treatment, Rotstop † , has been based on a single strain of P. gigantea that has been applied on more than 47,000 ha annually in Fennoscandia. This paper reports on the spread of genetic material from the Rotstop † bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, one must be aware that some of observed diversity within ITS might be due to the 454‐sequencing errors (Harismendy et al ., ), and those results, therefore, should be interpreted with caution. Nevertheless, in agreement with our results, a high genetic diversity in natural P. gigantea populations sampled from stumps and logs was reported previously, suggesting that biocontrol applications of genetically uniform P. gigantea are unlikely to cause any immediate threat to the genetic diversity of this fungal species (Vainio et al ., ; Samils et al ., ). In this study, the sites in which the ITS type of P. gigantea biocontrol strain was detected were 1–60 months old following harvesting of the trees and included both treated and nontreated sites (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, one must be aware that some of observed diversity within ITS might be due to the 454‐sequencing errors (Harismendy et al ., ), and those results, therefore, should be interpreted with caution. Nevertheless, in agreement with our results, a high genetic diversity in natural P. gigantea populations sampled from stumps and logs was reported previously, suggesting that biocontrol applications of genetically uniform P. gigantea are unlikely to cause any immediate threat to the genetic diversity of this fungal species (Vainio et al ., ; Samils et al ., ). In this study, the sites in which the ITS type of P. gigantea biocontrol strain was detected were 1–60 months old following harvesting of the trees and included both treated and nontreated sites (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the possibility should not be excluded that the biocontrol strain might persist in the soil for up to 60 months and also spread occasionally to the nontreated sites. For example in stumps treated with the biocontrol strain P. gigantea , it was found that this strain dominates the fungal communities for 4–5 years and then its abundance rapidly decreases (Vainio et al ., ; Vasiliauskas et al ., ) while its spread to adjacent stands is largely restricted (Samils et al ., ). However, the results of this study suggest that the relative abundance of P. gigantea belowground is not affected either by the time elapsed since the application of the biocontrol agent or by the treatment itself as in different sites it was generally low over time and did not significantly exceed the levels found in the controls (Table ).…”
Section: Discussionmentioning
confidence: 97%
“…in European and North American production forests (Pirttilä & Frank 2018). In Fennoscandia, the commercial biocontrol agent Rotstop® (Verdera Oy, Espoo, Finland), which is based on two strains of P. gigantea, is widely used (applied on 47 000 ha of forest land yearly) and known to influence the early colonizer community structure in treated stumps (Vasiliauskas et al 2005;Samils et al 2009). A Canadian strain of the wood-decay basidiomycete Chondrostereum purpureum has been developed into a biological herbicide Chontrol® (MycoLogic Inc., Victoria, Canada) to control stump sprouting and regrowth of deciduous tree stumps (Bailey 2010).…”
Section: Introductionmentioning
confidence: 99%